Energy yields of small grid connected photovoltaic system: effects of component reliability and maintenance. Issue 5 (1st July 2015) - Perdue, Michael; Gottschalg, Ralph
Abstract : The likelihood of system failure of small systems is investigated in order to establish the risk associated for the investment into a photovoltaic (PV) system for small domestic applications. This is achieved by reviewing existing literature on PV system failure rates and using these as an input for a statistical PV system yield simulation tool that considers failure and repair. It is typically assumed that these systems do not require any maintenance, but it is shown that this will have near catastrophic impact on the energy production of PV systems. The no maintenance is not a likely scenario, as small systems have to register their generation to achieve a feed‐in‐tariff. In a later stage, when PV is used for self‐consumption only, this may change but in the present market most users are forced to carry out a quarterly check and thus this catastrophic failure is avoided by the need of having to apply for the feed‐in‐tariff. Minimum maintenance strategies for ensuring profitable system operation are investigated and their cost‐effectiveness is discussed. It is shown that the present situation where many systems are neither monitored nor is any maintenance carried out results in a high probability of unsuccessful system operation as failure detection may take a very long time. Successful system operation here is defined as not recovering the financial investment. It would be advisable to carry out at least monthly performance checks as otherwise it is likely to have more than 10% energy lost because of system downtime. This requires, however, availability of irradiance data as otherwise it is not possible to identify whether low yields are due to resource issues or really system yield issues.